A Study on Applications of AI, ML, DL And Blockchain In Healthcare And Pharmaceuticals And It’s Future - Satwik, P.M; Geluvaraj, B; Kumar, T.A. Ashok (International Journal of Computer Sciences and Engineering, 2025)
Artificial Intelligence (AI), Blockchain (BC), Machine Learning (ML) and Deep Learning (DL) is a progressive step within pharmaceutical and healthcare business. It's not a dreamland degree of advance any more drawn out, it’s a functional instrument that can enable a relationship to propel their composed game-plan, improve the standard of concern, create more income, and reduction chance. AI and ML have a crucial part to play in increasing crafted by tranquilizing improvement specialists, so that as educated, to begin with, an examination of the mass of scientific data can be coordinated remembering the ultimate objective to outline essential new learning. AI has truly moved from concept towards verity in the pharmaceutical industry. The use of BC in health care is expected to stress the characteristic framework in unimaginable strategies to advantage the impacted individual and enhancements in the audit happens unmistakably thriving and costs. AI, MI, and DL are rapidly getting to be establishment technologies, like the web, and an ocean change of impact is ensured to take hold. Recurrent neural networks (RNNs), which be commonly suitable for sequence evaluation, are one of the largely confident tools for time-series or text investigation. And one of the most effective applications of RNNs in healthcare is digital scientific report analysis. In this script, we characterize the way innovation is moving Pharmaceutical and Healthcare companies and its future